Business Process Re-engineering is always framed to achieve good results when managerial and human-centred strategies of team-working are present. Discuss whether this is achieved in practice or not, and how? - Kwadade-Cudjoe, Francis (Archives of Business Research, 2021)
Business Process Re-engineering / Re-design (BPR) was introduced as the radical redesign of core business processes of organizations to enable them achieve dramatic improvement in service, performance, productivity and quality of products / services. It was touted in the 1990s as the newest business strategy to make management of businesses effective, after less was derived from TQM. Unfortunately, the application of the BPR strategy on businesses, example in the automobile industry, was only marginal but better than TQM. BPR was designed to re-organize organizational processes, and then make extensive use of Information Technology (IT) for running organizations. However, most of the localized organizations that adopted the BPR strategy for use, complained bitterly about the application. This was due to the fact that the managerial and human-centred strategies of team-working was not effectively achieved. However, for organizations that go global, it is a different ball game all together, as there are string of successes associated with them. Localized organizations should therefore, create the right enablement for the strategy to work, as some MNCs have been able to use BPR to achieve competitive advantage.